DAMPAK POSITIF DAN NEGATIF PERMAINAN GAME ONLINE DIKALANGAN PELAJAR - Suryanto, Rahmad Nico; Kadarisman, Yoskar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Online games users who have high self-control is able to regulate the use of online games that are not immersed in online games, are able to use online games as needed, able to integrate online activities with other activities in their lives. Instead, users of online games with low self-control is not able to direct and regulate his online behavior. They are not able to interpret stimuli encountered, and not able to choose the appropriate action. Based on the problems described above, the authors are interested in conducting research with the title: "Positive and Negative Impact of Online Gaming Amongst Students". Based on the background described above, the formulation of the problem in this study are as follows: 1) The characteristics of students who play online games. 2) What positive and negative effects of online game addiction among students. This study uses data collection techniques as follows: 1) Observation 2) interviews. Data analysis was done to answer the problem in this research is Descriptive Statistics. Based on the research results, the conclusion to this study are positive and negative effects of online game play among teens can be concluded that: 1) The characters of players who frequently play online games from 30 respondents most respondents are: a) students or young school school layout adjacent to the cafe, b) student male sex with 28 people, c) most respondents are students aged 13-17 years with a number of 22 people, and d) most respondents are students whose parents work as civil servants / employees with a number of 12 people. 2) Positive Impact, can eliminate the stress of school routine, the value of the most prominent subjects in the school computer, quickly resolve issues about (problem solving) in the lesson, and easy to get acquainted with new friends who have the same hobby. 3) Negative Impact, absenteeism to be able to play online games in Internet cafes, low academic achievement, use of improper spending money properly, rarely exercise in every week, and wasteful if you have money. Keywords: Positive Impact, Negative Impact, Game Online